Aplicación del proceso de atención de enfermería en paciente adulto de 53 años de edad con diagnóstico de síndrome coronario agudo sin elevación del segmento st en el área de medicina interna del Hospital Alfredo Noboa Montenegro. - Ortiz Sánchez, Carlos Armando (2020)
Acute coronary syndromes are formed by unstable angina pectoris and acute myocardial infarction with or without st segment elevation. These diseases are very common already worldwide so it is affecting a large part of the population. For the evaluation of these pathologies it is very necessary to know well what are its signs and symptoms that identify it such as chest pain or chest pain, difficulty breathing, vomiting and dizziness, indigestion, etc. Therefore, the interrogation and the complementary exams are of great help since here we can have a better diagnosis. This present work was carried out in order to demonstrate in a better way the pathophysiology, the causes, diagnosis, prevention and treatment of acute coronary syndrome.